2008
DOI: 10.1104/pp.108.131516
|View full text |Cite
|
Sign up to set email alerts
|

Karrikins Discovered in Smoke Trigger Arabidopsis Seed Germination by a Mechanism Requiring Gibberellic Acid Synthesis and Light    

Abstract: Discovery of the primary seed germination stimulant in smoke, 3-methyl-2H-furo[2,3-c]pyran-2-one (KAR1), has resulted in identification of a family of structurally related plant growth regulators, karrikins. KAR1 acts as a key germination trigger for many species from fire-prone, Mediterranean climates, but a molecular mechanism for this response remains unknown. We demonstrate that Arabidopsis (Arabidopsis thaliana), an ephemeral of the temperate northern hemisphere that has never, to our knowledge, been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
264
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(280 citation statements)
references
References 56 publications
(63 reference statements)
11
264
1
4
Order By: Relevance
“…Although karrikins can overcome primary dormancy (PD) in Arabidopsis thaliana seed, the effectiveness of KAR 1 on germination varies by ecotype and seed dormancy state: highly dormant seed has reduced response, whereas the rapid germination rates of nondormant seed can mask any positive influence from karrikin (25). KAR 1 does not recover germination of the ga1-3 mutant, which has no detectable GA biosynthesis, or enhance its sensitivity to exogenous GAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although karrikins can overcome primary dormancy (PD) in Arabidopsis thaliana seed, the effectiveness of KAR 1 on germination varies by ecotype and seed dormancy state: highly dormant seed has reduced response, whereas the rapid germination rates of nondormant seed can mask any positive influence from karrikin (25). KAR 1 does not recover germination of the ga1-3 mutant, which has no detectable GA biosynthesis, or enhance its sensitivity to exogenous GAs.…”
mentioning
confidence: 99%
“…Karrikins (KAR) have been established as a new class of signaling molecules in smoke from burning vegetation that trigger seed germination for many angiosperms (23)(24)(25)(26). Although karrikins can overcome primary dormancy (PD) in Arabidopsis thaliana seed, the effectiveness of KAR 1 on germination varies by ecotype and seed dormancy state: highly dormant seed has reduced response, whereas the rapid germination rates of nondormant seed can mask any positive influence from karrikin (25).…”
mentioning
confidence: 99%
“…(Nelson et al 2009). Further experiments showed that KAR 1 cannot overcome the requirement of germination for gibberellin (GA) biosynthesis, and indeed that KAR 1 might act in part by stimulating the expression of the GA biosynthetic genes GA3ox1 and GA3ox2, which would, in turn, stimulate germination (Nelson et al 2009). …”
Section: Karrikin Studies In Arabidopsismentioning
confidence: 99%
“…However, it was soon shown that the relationship was not so straightforward. First, although karrikins were potent germination stimulants of Brassica tournefortii, the synthetic strigolactone GR24 was not (Nelson et al 2009). Conversely, seed of the parasitic weed Orobanche minor responded strongly to GR24, but not at all to karrikins; this observation has since been extended to several other parasitic species .…”
Section: Karrikins Are Structurally Related To Strigolactonesmentioning
confidence: 99%
“…(5,7) Although the mode of action of smoke and 1 (and related karrikins) in promoting germination and vigor is currently unknown, research is progressing in this field. (4,8,9) Previous investigations of smoke-stimulated seed germination demonstrated that dilute solutions of smoke-water were highly effective in promoting the germination of light-sensitive seeds of Lactuca sativa L. cv. Grand Rapids.…”
mentioning
confidence: 99%